WASH: Highlighting Global Water, Sanitation, and Hygiene Initiatives. Issue 6 (November 2015) - Unknown
Abstract : Clean water is essential for optimal maternal child health outcomes in poor resource countries. Our expert on global health, Dr. Callister, describes the WASH initiative and what this means for health and wellness for families living in developing areas of the world.